The Effects of Conflict on the Performance of Production Section Employees at PT. YKT Gear Indonesia - Dwianto, Agung Surya; Rustomo, Rustomo; Pirmansyah, Yodi (JURNAL MANAJEMEN MOTIVASI, 2019)
Abstract Conflict is a mismatch between two or more members or groups (in an organization or company) that must share limited resources or work activities and/or because of the fact that they have different status, goals, values, or perceptions. Conflicts can occur anywhere, including in a company, conflict occurs because each party or one party feels disadvantaged. Conflicts can have negative consequences but can also have positive consequences. This research was conducted in a company, namely in PT YKT Gear Indonesia, the purpose of this study was to determine the extent of conflict can affect PT YKT Gear Indonesia's employees, whether the influence of conflict can reduce the performance of PT YKT Gear Indonesia's employees or can improve PT YKT Gear employee performance Indonesia. From the results of this study it can be concluded that based on the results of a simple regression analysis, conflict has a positive influence on employee performance that is equal to 0.344. This means that a one-point increase in Conflict will result in an increase in Employee Performance at PT YKT Gear Indonesia of 0.344 and vice versa, if there is a one-point decrease in Conflict, it will be followed by a decrease in Employee Performance of 0.344 at PT YKT Gear Indonesia. While based on the results of a simple correlation analysis the effect of conflict on performance is moderate positive because the resulting r value is 0.434. Based on the coefficient of determination it can be concluded that conflict has a contribution of 18.81% to the performance of PT YKT Gear Indonesia employees, the remaining 81.91% is influenced by other factors. Keywords: Conflict, Employee Performance